PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA MEDIA CAMPURAN GAMBUT DENGAN EFFLUENT DI PEMBIBITAN UTAMA - Handayani, Sutri; Amri, Al Ikhsan; Khoiri, M. Amrul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to observe the effect of deposited effluent application on land application in the peat medium on growth of palm oil seedlings in the main nursery. The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau, Jl. Bina Widya km 12.5 Simpang Baru Villae, Tampan District, Municipality of Pekanbaru. The experiment was conducted for 3  months, starts from February to April 2013. The research was conducted as experiments using Completely Randomized Design (CRD) non-factorial that consisting of 5 treatments and 3 replications. To see the differences between treatments tested Duncan New Multiple Range Test (DNMRT) at the 5% level. Parameters  were observed are increased seedling height, increased leaf number, increased diameter stump, root volume, dry weight ratio of roots and canopies of palm oil seedlings. Result of research  have shown that effluent application with various doses significantly affected all parameters.   Keywords: mixed media, Effluent, palm oil seedlings.